2022
DOI: 10.1007/s00233-022-10305-2
|View full text |Cite
|
Sign up to set email alerts
|

Identities of the stylic monoid

Abstract: We observe that for each n ≥ 2, the identities of the stylic monoid with n generators coincide with the identities of n-generated monoids from other distinguished series of J -trivial monoids studied in the literature, e.g., Catalan monoids and Kiselman monoids. This solves the Finite Basis Problem for stylic monoids.A monoid identity is a pair of words, i.e., elements of the free monoid X * over an alphabet X, written as a formal equality. An identity w = w ′ with w, w ′ ∈ X * is said to hold in a monoid M if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this note, we meet another cluster grouping around the 3-generated plactic monoid; as follows from a recent result in [5], this cluster also hosts the monoid of all upper triangular 3 × 3-matrices over the tropical semiring. For an example from the realm of finite monoids, see the author's recent note [9]. It is very tempting to understand the intrinsic reasons of this clustering phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In this note, we meet another cluster grouping around the 3-generated plactic monoid; as follows from a recent result in [5], this cluster also hosts the monoid of all upper triangular 3 × 3-matrices over the tropical semiring. For an example from the realm of finite monoids, see the author's recent note [9]. It is very tempting to understand the intrinsic reasons of this clustering phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The anonymous referee has also observed the following: In [63], it is shown that styl 3 is a homomorphic image of the Kiselman monoid Kis 3 and the Catalan monoid Cat 3 is a homomorphic image of styl 3 . It can be easily checked that these properties still hold when considering the mentioned monoids with involution.…”
Section: Remarkmentioning
confidence: 94%
“…Aird and Ribeiro have given a faithful representation of the stylic monoid and its involution case of each finite rank, and then solved the finite basis problems for them [5]. Also, Volkov has solved the finite basis problem for the stylic monoid by different mean [52]. The identity checking problems for the Baxter, sylvester and stylic monoids have been considered [5,14], which can be done in polynomial time.…”
Section: Introductionmentioning
confidence: 99%